Daily milk yield and its predictors in dairy cows in Jinka city of Ari Zone, Southern Ethiopia - A.S. Kenasew; A.A. Kerkela (Journal of Veterinary and Animal Sciences)
A cross-sectional study was conducted in Jinka City, Ari Zone, Southern Ethiopia, from May 2024 to January 2025 to determine the daily milk yield and assess its predictors. The study revealed that the average milk yield was 18.13, 14.5, and 14.47 litres in Arkisha, Mehal Ketema, and Tenadam respectively. There was a significant difference in daily milk yield among the three sub-cities of Jinka City (Mehal Ketema, Arkisha, and Tenadam). Body condition and parity were among the predictors that caused an increase in daily milk yield with a unit increase of predictors. As milk yield is influenced by numerous factors in the study area, appropriate management practices during production are crucial to enhance milk production and the profitability of production. Regular follow-up for the output change, provision of production-specific nutrients, and using an appropriate breeding program were recommended.